2019
DOI: 10.5267/j.ac.2018.6.003
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between governmental accounting education and practice

Abstract: Preparing well educated accounting students for future, involve teaching using high techniques, will benefit all public and private organizations. Accounting educators and practitioners are pressured by the industries, globalization and the professions to generate graduates with accountancy skills that meet the changing needs. In this survey, a questionnaire was conducted and distributed randomly to ascertain the views of accounting academics and practitioners on the contents of governmental accounting courses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
(6 reference statements)
1
2
0
1
Order By: Relevance
“…The findings also indicate that all three explanatory independent factors (integration, utilization and acquisition) are included in the regression equation. This result was supported by similar results of previous studies, such as Kuntjoro (2013), Nurhayati (2014), Andekina and Medeni (2013) and Ahmed (2019). The third hypothesis was suggested o identify the impact of the quality of accounting information on BP.…”
Section: Discussion Contributions and Implicationssupporting
confidence: 86%
“…The findings also indicate that all three explanatory independent factors (integration, utilization and acquisition) are included in the regression equation. This result was supported by similar results of previous studies, such as Kuntjoro (2013), Nurhayati (2014), Andekina and Medeni (2013) and Ahmed (2019). The third hypothesis was suggested o identify the impact of the quality of accounting information on BP.…”
Section: Discussion Contributions and Implicationssupporting
confidence: 86%
“…Bu durum Türkiye'de devlet muhasebesi eğitiminin olmadığına ya da eksik olduğuna bir işaret olarak algılanabilir. Nitekim yabancı literatürde konu ile ilgili çalışmalar (Ahmed, 2019;Wilson, 2013;Miller, 2006) mevcuttur. Soz konusu eğitim sayesinde ayrıca muhasebe uygulamalarırın esas unsuru olan insanın (Altunay ve Kuyumcu, 2021) devlet muhasebesi açısından etik davranmasına olanak sağlanabilir.…”
Section: -unclassified
“…Weshah (2021) recommended that universities should employ faculty members who have practical experience to teach CA courses. Ahmed (2019) found that in the UAE, practitioners emphasized conventional accounting practices, while academics emphasized contemporary techniques. Spring (2015) recommended that more heterodox, innovative, critical and in-depth studies of the use of computerized technology in education are encouraged in the GCC region.…”
Section: The Broad Concept Of Camentioning
confidence: 99%